Pengaruh Aplikasi Pupuk Hayati, Vermikompos Dan Pupuk Anorganik Terhadap Kandungan N, Populasi Azotobacter sp. Dan Hasil Kedelai Edamame (Glycine max (L.) Merill) Pada Inceptisols Jatinangor. - Mieke Rochimi Setiawati; Emma Trinurani Sofyan; Anne Nurbaity; Pujawati Suryatmana; Gordon Pius Marihot (Faculty of Agriculture, Pattimura University, 2017)
In Indonesia, Inceptisols is the largest soil order on which intensive agriculture is done. The fertility of this soil order is low, so that it is necessary to improve the soil fertility by using biofertilizers and organic matter. The objectives of this experiment were to determine the effect of a biofertilizer that contains microbe Azotobacter sp., Vermicompost and N, P, K Fertilizer on N content, the population of Azotobacter sp., and the yield of the Edamame soybeans at Inceptisols Jatinangor. A Field experiment was conducted by using Randomized Blocked Design consisted of 10 treatments and three replication. The combinations of these treatments consisted of: control (no treatment), the dose recommendation Urea 100 kg ha-1 + SP36 150 kg ha-1 + KCl 125 kg ha-1, 5 ton ha-1 vermicompost + ½ recommendation ha-1 N, P, K, 5 ton ha-1 vermicompost + 1 recommendation ha-1 N, P, K, 5 ton ha-1 vermicompost + 1½ recommendation ha-1 N, P, K, 10 ton ha-1 vermicompost + ½ recommendation ha-1 N, P, K, 10 ton ha-1 vermicompost + 1 recommendation ha-1 N, P, K, 10 ton ha-1 vermicompost + 1½ recommendation ha-1 N, P, K, 5 ton ha-1 vermicompost + ½ recommendation ha-1 N, P, K + liquid biofertilizers 5 L ha-1, 10 ton ha-1 Vermicompost + ½ recommendation ha-1 N, P, K + liquid biofertilizers 5 L ha-1. The experimental results showed that the combined treatment of liquid biofertilizer, Vermicompost and N, P, K fertilizer enhanced the population of Azotobacter sp. and weight of soybean but did not significantly influence N uptake.